The Effect of Fish Flour Replacement with Golden Snail Flour on The Giblets of Male Bali Duck - D, Oktaviantoro; Puger, A. W.; Puspani, E. (Jurnal Peternakan Tropika, 2019)
This study aims to determine the effect of fish meal replacing with golden snail flour in the rations on thegibletsof malebali ducks. The design used a Randomized Block Design (RBD) consisting of 5 treatments, namely: the ration containing 15% fish meal as control (R0); the replacement of fish meal with 25% golden snail flour (R1), the replacement of fish meal with 50% golden snail flour (R2), the replacement of fish meal  with 75% golden snail flour (R3) end the replacement of fish meal  with 100% golden snail flour (R4).   Each treatment used 4 blocks as replicate, each block consists of 1 male bali duck with of 1 month age. The variables observed were the percentage of gizzard, small istentine, large intestine, heart, liver, pancreas and spleen. The results showed that the replacement of fish meal with golden snail flour in rations up to 100% were not significantly different (P>0.05) on the ariables observed compared to control. It can be concluded that the fish meal replacement with golden snail flour in male bali ducks aged 10 weeks to level 100% does not affect the organs in male bali ducks .   Keywords: Giblets , Ducks, Fish Flour and golden Snail Flour.